2019
DOI: 10.3390/chemistry1010004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Two-Dimensional Nanomaterials for Laser Protection

Abstract: The Nobel Prize in Physics 2018, “For groundbreaking inventions in the field of laser physics”, went to Arthur Ashkin and Gérard Mourou and Donna Strickland. Their inventions have revolutionized laser physics and greatly promoted the development of laser instruments, which have penetrated into many aspects of people’s daily lives. However, for the purpose of protecting human eyes or optical instruments from being damaged by both pulsed and continuous wave laser radiation, the research on laser protective mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 124 publications
(144 reference statements)
0
12
0
5
Order By: Relevance
“…[ 14 ] Apart from graphene, many other new 2D materials have been introduced such as transition metal nitrides and carbides (MXene), various transition metal dichalcogenides (TMDs) and hexagonal boron nitride (h‐BN). They have discrete electrical, [ 15 ] thermal, [ 16 ] optical [ 17 ] and electromagnetic characteristics, [ 18 ] combined with robustness and mechanical flexibility giving an excellent path toward making composites with tailored multifunctional properties. [ 19 ] Among 2D nanofillers, BN as a filler material has captivated enormous researchers because of its interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Apart from graphene, many other new 2D materials have been introduced such as transition metal nitrides and carbides (MXene), various transition metal dichalcogenides (TMDs) and hexagonal boron nitride (h‐BN). They have discrete electrical, [ 15 ] thermal, [ 16 ] optical [ 17 ] and electromagnetic characteristics, [ 18 ] combined with robustness and mechanical flexibility giving an excellent path toward making composites with tailored multifunctional properties. [ 19 ] Among 2D nanofillers, BN as a filler material has captivated enormous researchers because of its interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, it has been challenging in identifying or developing suitable materials to exhibit OL at a controlled threshold of laser intensity. [1][2][3][4][5] Due to the same reason, the mechanism of OL has also remained an active research field. Optical limiting is generally regarded as a nonlinear optical phenomena because it can be induced by nonlinear absorption or scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Optical limiting is generally regarded as a nonlinear optical phenomena because it can be induced by nonlinear absorption or scattering. [1][2][3][4][5] Recently, atomically thin 2D nanomaterials have emerged as novel optoelectronic materials with strong nonlinear optical properties. [6][7][8][9][10] As an important application, OL has been reported in liquid suspensions of graphene, 3,5,[11][12][13][14][15][16][17][18][19] graphene oxide (GO), 3,18,[20][21][22][23][24][25][26][27][28][29] transition metal dichalcogenides (TMD), 4,[30][31][32][33][34][35][36] and black phosphorous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past few years, efficient synthetic strategies have been established for the fabrication of polyaromatic hydrocarbons (PAHs) incorporating stoichiometric boron nitride sections (B n N n ) in their structure. Most of the reported attempts aim to deliver doped PAHs to be used either as stand-alone functional-modules or as precursors of more complex architectures of high technological value, such as two-dimensional graphene-like materials of nonzero bandgaps. , The principal target in this research area is to improve and fine-tune the optoelectronic properties of planar polyaromatic hydrocarbons (e.g., graphenes) using as doping agents foreign units (e.g., borazine) that could homogeneously blend in their framework without causing undesired structural distortions. To this end, Krieg et al reported the synthesis of doped hexabenzocoronene in which the central aromatic sextet is replaced by a borazine ring.…”
Section: Introductionmentioning
confidence: 99%